1986
DOI: 10.1038/bjc.1986.147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium supplementation in testicular cancer patients receiving cis-platin: A randomised trial

Abstract: Summary The concentration of magnesium in serum has been shown to fall to potentially dangerously low levels after several courses of treatment with cis-diamminedichloroplatinum II (cis-platin). The aims of this study were to examine the effects of magnesium supplementation on predicted outcome of treatment, rate of response to treatment and toxicity of treatment. Sixteen patients with testicular cancer were studied in detail over a 14 month period. One patient with an ovarian dysgerminoma was also included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 8 publications
4
58
0
1
Order By: Relevance
“…Although detailed tissue types were not considered in the present study, the results regarding increases in PTH or PTH-rP levels in patients with ESCC may be associated with this specificity. However, previous studies reported that Mg supplementation did not affect the tumor response to cisplatin-based chemotherapy (9,11,25). It was also concluded in the present study that Mg supplementation did not affect the efficacy of cisplatin-containing chemotherapy, as the overall survival time was similar between the patients with or without Mg supplementation (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Although detailed tissue types were not considered in the present study, the results regarding increases in PTH or PTH-rP levels in patients with ESCC may be associated with this specificity. However, previous studies reported that Mg supplementation did not affect the tumor response to cisplatin-based chemotherapy (9,11,25). It was also concluded in the present study that Mg supplementation did not affect the efficacy of cisplatin-containing chemotherapy, as the overall survival time was similar between the patients with or without Mg supplementation (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…1 and Table II). The protective effects of oral or intravenous Mg supplementation against cisplatin-induced nephrotoxicity have been reported in various types of malignancy, including in lung (10-12), head and neck (10,23,24), digestive (8,10), testicular (25), ovarian (9,24) and bladder (24) cancer. However, just a limited number of clinical reports have demonstrated the protective effects of intravenous Mg supplementation against cisplatin-induced nephrotoxicity in ESCC (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the association of cisplatin toxicity with the depletion of serum magnesium, and magnesium supplementation was adopted to prevent hypomagnesemia during drug treatment (27). Hypomagnesemia was observed in humans (28) and in experimental animals (29). It was reported that in cisplatin-treated mice the urinary magnesium waste almost doubled (30), and the magnesium depletion was shown to enhance cisplatin nephrotoxicity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Second, several previous studies reported that intravenous supplementation with Mg (magnesium) can prevent CIN. 26,38,39) Because our treatment protocol did not include Mg administration, we cannot state its efficacy in patients with these risk factors. Third, we defined the patients with a history of the cardiac disease such as angina and myocardial infarction as patients with cardiac disease in this study.…”
Section: Discussionmentioning
confidence: 99%